Gas adsorption and selectivity studies for porous metal-organic frameworks - Gao, Shan (2016)
This thesis describes research on the preparation and characterisation of porous metal-organic framework (MOF) materials for gas storage and separation applications, with particular focus on light hydrocarbons. This work is of great importance in the structural flexibility studies of MOF materials upon the physisorption of gas molecules. It also involves comprehensive gas sorption and separation studies of a Zr-based MOF, MFM-601, with a pioneering investigation for NH3 uptakes for this species of MOFs.